إذا الفجائيّة وآراء النُّحاة فيها (Comprehensive Journal of Science, 2026)
The field of grammatical particles in Arabic linguistics exhibits a wide diversity of tools with multiple significations that perform various functions depending on the context in which they appear. Scarcely does an Arabic sentence lack a particle that contributes to clarifying, emphasizing, or embellishing its meaning, both phonetically and semantically.One of the most prominent of these particles is (*The Sudden "Idha" / Idha al-Fuja'iyyah*), which is the subject of this research. This study is concerned with examining its significance, its positions, and the structure of the sentence following it. It also explores the divergent views of grammarians regarding its classification; one group considers it a particle (Harf) with no grammatical position, others view it as an adverb of time (Zarf Zaman), while some classify it as an adverb of place (Zarf Makan). Each group presented evidence and arguments that contributed to enriching the scholarly debate surrounding it.Based on this multiplicity of opinions regarding the Sudden "Idha," I found it necessary to investigate this topic by reviewing primary grammar books and extrapolating evidence from the Holy Qur’an and Arabic speech. The methodology adopted in this research is the descriptive-analytical approach.
Keywords: Sudden Idha (Idha al-Fuja'iyyah) - Significance - Grammatical Structure - Conditional Idha